2012
DOI: 10.1590/s0103-50532012000600021
|View full text |Cite
|
Sign up to set email alerts
|

PtSnIr/C anode electrocatalysts: promoting effect in direct ethanol fuel cells

Abstract: Este estudo investiga o efeito promotor de anodos eletrocatalisadores do tipo PtSnIr/C (1:1:1), preparados pelo método de precursor polimérico, na reação de oxidação de etanol em uma célula a combustível de etanol direto (DEFC). Todos os materiais usados foram metal 20% m/m com relação a carbono. Análise por espectroscopia fotoelétrica de raios X (XPS) mostrou a presença de Pt, PtOH 2 , PtO 2 , SnO 2 e IrO 2 na superfície do eletrocalisador, indicando uma possível estrutura de partícula revestida. Análise por … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The observed shift indicates a lattice constriction due to the incorporation of smaller Rh atoms into the Pt fcc structure, suggesting the alloy formation of Pt-Rh. In order to confirm the alloy formation, the 220 crystal planes were deconvoluted and the lattice parameters were calculated for all synthetized materials, as already reported on the literature [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…The observed shift indicates a lattice constriction due to the incorporation of smaller Rh atoms into the Pt fcc structure, suggesting the alloy formation of Pt-Rh. In order to confirm the alloy formation, the 220 crystal planes were deconvoluted and the lattice parameters were calculated for all synthetized materials, as already reported on the literature [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…[88][89][90][91][92][93][94][95][96][97] Excluding Pt-Ru-Ir [90] and Pt-Cu-Ir, [91] all papers focused on Pt-Sn-Ir catalysts, that is, on the addition of Ir to benchmark Pt-Sn. [88][89][90][91][92][93][94][95][96][97] Excluding Pt-Ru-Ir [90] and Pt-Cu-Ir, [91] all papers focused on Pt-Sn-Ir catalysts, that is, on the addition of Ir to benchmark Pt-Sn.…”
Section: Ternary Pt-m-ir Catalystsmentioning
confidence: 99%
“…[88] Thus, formation of a Pt-Sn alloy is revealed by the increase of the lattice parameter, but the formation a ternary PtSnIr alloy as well as the presence of Sn and Ir oxides cannot be discarded. [92] DEFC tests at 90-110 8C with Pt-Sn-Ir/C as anode catalysts [88,93,94,96] showed that Ir presence enhances the EOR activity of Pt-Sn/C. Indeed, the binary Pt-Sn/C and ternary Pt-Sn-Ir/C catalysts give better results than the binary Pt-Ir/C and pure Pt/C.…”
Section: Ternary Pt-m-ir Catalystsmentioning
confidence: 99%
See 2 more Smart Citations